Mother Tongue Inclusion in Curriculum and Experiences of Local Stakeholders - Paudel, Govinda Prasad (Bhashalok भाषालोक, 2026)
The purpose of this article is to explore the local stakeholders’ experiences on local curriculum designing and implementing process at basic level school. For this purpose, interpretive paradigms are applied as research methodology. Research fields and participants were chosen on the basis of purposive sampling from Bhaktapur municipality. The primary and secondary information was collected and information was interpreted through interpretive inquiry as a tool of qualitative approach. This research goes on to argue that Local Curriculum (LC) is constructed as local subject or mother tongue as a subject or means of instruction through the participation of local stakeholders such as head teacher, teacher, and parents as well. In this line, the Government of Nepal has made a policy for preparing and implementing LC in each school accordingly as their local need. In spite of it, a few schools are practicing LC in the classrooms. Thus, there is a gap between policy and practice of LC making and implementing practice in basic level school. Thus, this research explores the actual practice of designing and executing LC at the classroom.